Ralph Waldo Emerson’s Approach to Ecology (The Batuk, 2020)
This article attempts to explore Emerson’s trust in nature and his efforts to establish strong affinity between human being and natural world using the tool of eco criticism. Ecological study attempts to elaborate the significance of nature for the benefit of human beings. Protecting nature means protecting the life of human beings because when the nature is destroyed, it eventually hampers the daily life of human individuals. Nature writers have honestly recognized the value of nature to encourage people to love it and understand its value. Living beings undergo several experiences in the company of nature and they maintain their miseries and happiness which come side by side. Therefore, it is essential that human beings must honestly attempt to strengthen their understanding with the environmental issues.